Low electromagnetic emission wireless network technologies : 5G and beyond - Imran, Muhammad Ali; Héliot, Fabien; Sambo, Yusuf Abdulrahman, 1988- (IET telecommunications series ;, 2019)
The book has 12 chapters and is divides into 2 parts. The first part which is about EMF evaluation and characterisation; deals with EMF exposure definition, metrics, effects and regulations; Electromagnetic field (EMF) monitoring tools; Large-scale EMF characterization considering real network deployments; EMF exposure in heterogeneous networks environments; and Architecture of public mobile networks and its impact on EMF exposure. The second part which is about EMF reduction techniques; covers EMF emission-aware resource allocation for uplink OFDM systems; Multicell uplink scheduling for EMF emission minimization in OFDMA systems; EMF: RF device end of things - low-exposure user terminal radio design concepts; Millimetre-wave flexible wearable antenna design and challenges for 5G and beyond; Reducing EMF emissions in ultra-reliable low-latency communications with HARQ; and Reducing EMF via energy-efficient inter-frequency small cell discovery. Conclusions and future perspectives are also given